Linking at-risk South African girls to sexual violence and reproductive health services: A mixed-methods assessment of a soccer-based HIV prevention program and pilot SMS campaign. (October 2018) - Merrill, Katherine G.; Merrill, Jamison C.; Hershow, Rebecca B.; Barkley, Chris; Rakosa, Boitumelo; DeCelles, Jeff; Harrison, Abigail
Highlights: A soccer-based program for adolescent girls in a South African township shows promise. Modest improvement in gender attitudes, self-efficacy, communication, HIV knowledge, stigma. Key intervention components are the coach-participant relationship, safe space, and soccer. Programs like SKILLZ Street are needed for at-risk adolescent girls in such settings. Further engagement of teachers, parents, and male students in girls' programming is needed. Abstract: Grassroot Soccer developed SKILLZ Street —a soccer-based life skills program with a supplementary SMS platform—to support adolescent girls at risk for HIV, violence, and sexual and reproductive health challenges. We conducted a mixed-methods assessment of preliminary outcomes and implementation processes in three primary schools in Soweto, South Africa, from August to December 2013. Quantitative methods included participant attendance and SMS platform usage tracking, pre/post questionnaires, and structured observation. Qualitative data were collected from program participants, parents, teachers, and a social worker during 6 focus group discussions and 4 in-depth interviews. Of 394 participants enrolled, 97% (n = 382) graduated, and 217 unique users accessed the SMS platform. Questionnaires completed by 213 participants (mean age: 11.9, SD: 3.02 years) alongside qualitative findings showed modest improvements in participants' perceptions of power in relationships and gender equity, self-esteem, self-efficacy to avoid unwanted sex, communication with others about HIV and sex, and HIV-related knowledge and stigma. The coach-participant relationship, safe space, and integration of soccer were raised as key intervention components. Implementation challenges were faced around delivery of soccer-based activities. Findings highlight the relevance and importance of programs like SKILLZ Street in addressing challenges facing adolescent girls in South African townships. Recommendations for future programs are provided.